Reliable Designing of Stand-alone PV/FC Hybrid System - Saber Arabi Nowdeh; A. Rajabi Ghahnavieh; H. Shojaei (Majlesi Journal of Electrical Engineering)
Application of renewable energy sources have shown perfect potential as a form of contribution to conventional power generation systems. This paper presents an hybrid system based on photovoltaic (PV) module and PEM (proton exchange membrane) fuel cell (FC) with the aim of selling electricity to distribution network (DN) and improve its reliability. In this paper proposed system, moreover supply the load electricity of system, capable to sale electricity to DN and by electricity injection causes DN reliability improvement. The revenue from selling electricity to DN is considered as the system profit (SP). An optimization to maximize the SP using GAMS environment is applied. This study claims that moreover load electricity provision, electricity can also be sold to DN by proposed hybrid system and by injection the electricity to that increased, its reliability in consumer load supplement.